2014
DOI: 10.3346/jkms.2014.29.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Mercury Intake and Blood Mercury Level in Korea

Abstract: This study was performed to evaluate the effect of dietary factors for mercury exposure by comparing with blood mercury concentration. Study population consisted of 1,866 adults (839 men and 1,027 women) in randomly-selected 30 districts in southeast Korea. Dietary mercury intake was calculated from food frequency questionnaire (FFQ) on seafood items and 24 hr recall record. Blood mercury concentration was measured with atomic absorption spectrometry. Mean age of the subjects was 43.5 ± 14.6 yr. The FFQ showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…The main source of human mercury exposure is known to be mercury contaminated fish and shellfish. The higher levels of mercury and methylmercury in our study than in the previous studies from Western countries might be explained by the presence of lifestyle risk factors for mercury exposure in Korea, such as high seafood consumption [ 22 ]. As an example with high seafood consumption country like Korea, Sakamoto et al has reported that the mean maternal RBCs level of lead and mercury were 26.4 ng/g and 9.41 ng/g from Japanese women [ 23 ].…”
Section: Discussionmentioning
confidence: 52%
“…The main source of human mercury exposure is known to be mercury contaminated fish and shellfish. The higher levels of mercury and methylmercury in our study than in the previous studies from Western countries might be explained by the presence of lifestyle risk factors for mercury exposure in Korea, such as high seafood consumption [ 22 ]. As an example with high seafood consumption country like Korea, Sakamoto et al has reported that the mean maternal RBCs level of lead and mercury were 26.4 ng/g and 9.41 ng/g from Japanese women [ 23 ].…”
Section: Discussionmentioning
confidence: 52%
“…Third, sources of inorganic Hg, typically inhalation of vaporized gas in industrial settings and dental amalgams, were not considered in this study. 9) While previous studies have reported fish consumption to be the primary source of Hg in Korea, You et al 7) reported that dietary Hg intake was relatively weakly correlated with blood Hg concentrations. According to Kim and Lee, 24) no significant association between blood Hg and dental amalgam treatment was observed in a study based on KNHANES data.…”
Section: Discussionmentioning
confidence: 98%
“…5 6) Methylmercury, the predominant form of organic Hg, accumulates up the food chain and becomes the main food source of Hg exposure in humans. 7) Blood Hg concentration is considered the most valid biomarker of recent methylmercury exposure. 8 ) Due to growing societal concerns about environmental heavy metals in Korea, heavy metal biomonitoring has been performed since the third Korean National Health and Nutritional Examination Survey (KNHANES).…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of Pb exposures for populations residing in middle to low income countries include emissions associated with artisanal mining and processing activities, toxic waste sites, leaded paint and remaining leaded gas use [18,19,20,21]. Fish, shellfish and grains such as rice can be significant sources of Hg exposures [22,23]. Methyl mercury (MeHg) contributes the bulk of Hg exposures in most individuals; notably through the consumption of long-living, predatory fish species [24].…”
Section: Introductionmentioning
confidence: 99%